Effect of zinc supplementation on freshwater plankton density - Taneja, S K; ., Rashmi (Indian Journal of Fisheries, 2011)
The role of Zn in biological system is well known. However, its importance in plankton abundance has not been recognized conclusively. Accordingly, the influence of Zn on plankton density in a closed system was investigated keeping physico-chemical factors conducive to them. The results are reported in this paper.